Synthetic biology applied in the agrifood sector: Societal priorities and pitfalls - Frewer, L.J.; Coles , D.; Dijkstra, A.M.; Kuznesof, S.; Kendall, H.; Kaptan, G. (Applied Studies in Agribusiness and Commerce, 2016)
Synthetic biology offers potential for innovation in the agrifood sector, although concerns have been raised consumer rejection of applications will occur similar to that associated with the introduction of genetically modified foods. Risk-benefit assessment should address socio-economic, as well as health and environmental impacts. Ethical issues may be of particular relevance to the application synthetic biology, and may also resonate with societal concerns. A case-by-case analysis of relevant issues may be needed, and innovation must be driven by societal and consumer preferences as well as technological possibilities. Research into consumer and societal priorities is required early in the innovation trajectory.